Evaluating the Geylang East Community Library's young people collection. - Chua, Sharen Sze Yin. (2008)
This study sought to obtain information about whta the teenage users of the Geyland East Community Library sought, and if the fiction, non-fiction and magazine collections, as well as the Young People's Collection as a whole ere meeting their needs through measuring their satisfaction with the different collections.